Genetic and genomic approaches to identify genes involved in flagellar assembly in Chlamydomonas reinhardtii - Lin, Huawen (Methods Cell Biol, 2015)
Flagellar assembly requires intraflagellar transport of components from the cell body to the flagellar tip for assembly. The understanding of flagellar assembly has been aided by the ease of biochemistry and the availability of mutants in the unicellular green alga, Chlamydomonas reinhardtii. In this chapter, we discuss means to identify genes involved in these processes using forward and reverse genetics. In particular, the ease and low cost of whole genome sequencing (WGS) will help to make gene identification easier and promote the understanding of this important process.